2015
DOI: 10.1016/j.plipres.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols: Friend or foe in CNS disorders?

Abstract: In mammals, the central nervous system (CNS) is the most cholesterol rich organ by weight. Cholesterol metabolism is tightly regulated in the CNS and all cholesterol available is synthesized in situ. Deficits in cholesterol homeostasis at the level of synthesis, transport, or catabolism result in severe disorders featured by neurological disability. Recent studies indicate that a disturbed cholesterol metabolism is involved in CNS disorders, such as Alzheimer's disease (AD), multiple sclerosis (MS), and amyotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 227 publications
(335 reference statements)
0
50
0
Order By: Relevance
“…Their chemical structure consists of a sterol body; a cyclopentanoperhydro-phenanthrene ring system (formed by four rigid rings) with a hydroxyl group at position C-3 and a side chain attached to the carbon C-17 ( Figure 2C). Differences in the nature of the side chain gives a plethora of diverse sterols in plants, accounting to more than 260 different ones, as described over the last decades (Vanmierlo et al, 2015). The most abundant phytosterols in human diet are β-sitosterol, campesterol, campestanol, and stigmasterol.…”
Section: Phytosterols (Plant Sterols and Stanols)mentioning
confidence: 99%
“…Their chemical structure consists of a sterol body; a cyclopentanoperhydro-phenanthrene ring system (formed by four rigid rings) with a hydroxyl group at position C-3 and a side chain attached to the carbon C-17 ( Figure 2C). Differences in the nature of the side chain gives a plethora of diverse sterols in plants, accounting to more than 260 different ones, as described over the last decades (Vanmierlo et al, 2015). The most abundant phytosterols in human diet are β-sitosterol, campesterol, campestanol, and stigmasterol.…”
Section: Phytosterols (Plant Sterols and Stanols)mentioning
confidence: 99%
“…Based on the finding that the majority of plant sterols are carried in the HDL fraction, it was suggested that SR-B1 may play an important role. These HDL receptors are expressed by the apical endothelial cells of the BBB and could be involved in phytosterol transfer from blood into brain parenchyma (Vanmierlo et al, 2015).…”
Section: Plant Sterols In Brain and Their Relation To Neurological DImentioning
confidence: 99%
“…The mechanism by which glycosylated sitosterol possesses these harmful effects is not clear. It is speculated that it may occur through LXRβ disabling or through hindering mitochondrial function (Vanmierlo et al, 2015).…”
Section: Plant Sterols In Brain and Their Relation To Neurological DImentioning
confidence: 99%
“…In the complex process of cholesterol biosynthesis the first steroid intermediate lanosterol can be converted to cholesterol through two alternative pathways: the Bloch pathway via desmosterol, a direct cholesterol precursor, and the Kandutsch-Russell pathway via lathosterol. The disturbance in cholesterol homeostasis underlies many neurodegenerative diseases, and with aging represents a major risk factor for the development of such pathologies (Valenza et al 2007;Popp et al 2013;Vanmierlo et al 2015). Data regarding brain cholesterol metabolism in the course of aging are somewhat inconsistent (reviewed in Martin et al 2010).…”
Section: Introductionmentioning
confidence: 99%